2015
DOI: 10.1111/obr.12287
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of active video games on health outcomes among children and adolescents

Abstract: This meta-analysis synthesizes current literature concerning the effects of active video games (AVGs) on children/adolescents' health-related outcomes. A total of 512 published studies on AVGs were located, and 35 articles were included based on the following criteria: (i) data-based research articles published in English between 1985 and 2015; (ii) studied some types of AVGs and related outcomes among children/adolescents and (iii) had at least one comparison within each study. Data were extracted to conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
174
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 69 publications
13
174
1
5
Order By: Relevance
“…One study included in that review, but which was excluded from the present review (as it didn't compare AVGs to traditional exercise or to rest), found the HR target for moderate physical activity (64% of predicted maximum HR) was met during the boxing activity of the Likewise, the results of the present review are consistent with a meta-analysis of AVGs for healthy adults and children by Peng et al [66], who concluded that the HR, energy expenditure and oxygen consumption were no different between AVGs and traditional physical activities. In contrast, a more recent meta-analysis on AVGs in healthy children [67] found that AVGs had a large positive mean effect on HR, small positive mean effect size on enjoyment and a similar rate of perceived exertion compared to traditional exercise in a laboratory setting.…”
Section: Discussionmentioning
confidence: 79%
“…One study included in that review, but which was excluded from the present review (as it didn't compare AVGs to traditional exercise or to rest), found the HR target for moderate physical activity (64% of predicted maximum HR) was met during the boxing activity of the Likewise, the results of the present review are consistent with a meta-analysis of AVGs for healthy adults and children by Peng et al [66], who concluded that the HR, energy expenditure and oxygen consumption were no different between AVGs and traditional physical activities. In contrast, a more recent meta-analysis on AVGs in healthy children [67] found that AVGs had a large positive mean effect on HR, small positive mean effect size on enjoyment and a similar rate of perceived exertion compared to traditional exercise in a laboratory setting.…”
Section: Discussionmentioning
confidence: 79%
“…For instance, these studies often have small sample-sizes, do not take into account cultural or other demographical differences, and are undertaken over a short period [180,181,182]. Furthermore, several meta-analyses demonstrated a range of mostly positive results in regards to efficacy in the fields of exercise [183], promoting healthy lifestyles [184], and diabetes self-management [185]. Therefore, we can see the same challenges in healthcare that are apparent in educational and other contexts within this chapter -satisfactorily proving the efficacy of an amorphous medium across multiple use-cases.…”
Section: Healthcarementioning
confidence: 99%
“…They provide accompanying virtual agents or mirror the actions of the user [2]. The shift of focus from workout to play in games is believed to increase people's and specially children's exercising motivation because they "capitalize on children's natural interest in computerized video interaction" [3]. However, the long-term effects of exergaming with entertainment systems is contented [3].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of motivation is the most common obstacle for physical activity. Recently, there is a trend for using active video games to promote rehabilitation and physical activity [3]. These approaches seem to be a suitable addition to standard methods of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation